Effect of Electroacupuncture at Baihui Acupoint on Magnetic Resonance Spectroscopy and Spatial Learning and Memory Ability in APP/PS1 Transgenic Mice - Yingzheng ZHANG; Peiyuan ZHUO; Ruhui LIN; Lidian CHEN (康复学报)
Objective:To investigate the effects of electroacupuncture (EA) at Baihui (DU20) acupoint on learning and memory ability and1H magnetic resonance spectroscopy (1H-MRS) in APP/PS1 transgenic mice.Methods:A male APP/PS1 transgenic mice mated with a wild type female mice and 15 bred APP/PS1 transgenic mice identified by PCR were randomly divided into the model group (n=7) and the EA group (n=8) according to a random number table, and 8 age-matched littermates were divided into the control group. The EA group received EA at Baihui acupoint for 4 weeks. Morris water maze was used to test spatial learning and memory ability in the fourth week. NAA, Glu of the hippocampus were detected by1H-MRS.Results:Compared with the model group, the level of NAA and Glu were significantly increased (P<0.05). The EA group also ameliorated spatial learning and memory ability (P<0.05).Conclusion:EA at Baihui acupoint can improve spatial learning and memory ability inAPP/PS1 transgenic mice, the mechanism may be associated with the increasing NAA and Glu of the hippocampus.